2013
DOI: 10.1111/jpc.12263
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐cultural differences in Australian primary school children's weight and weight‐related behaviours

Abstract: The results indicate the need for obesity prevention initiatives to specifically target and reach children from low SES and Asian and Middle-Eastern backgrounds, and the importance of ensuring that such initiatives are culturally appropriate and address relevant issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…This is consistent with other research that shows children experiencing socioeconomic disadvantage have lower quality diets and higher intakes of junk foods and beverages [26, 27]. A recent study from NSW showed that, among low SES children, there were also clear differences in weight and weight-related behaviours according to cultural background [28]. While it has been shown that parents of children from Middle Eastern cultural backgrounds generally encouraged healthy behaviours, they also reported making regular exemptions [29].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with other research that shows children experiencing socioeconomic disadvantage have lower quality diets and higher intakes of junk foods and beverages [26, 27]. A recent study from NSW showed that, among low SES children, there were also clear differences in weight and weight-related behaviours according to cultural background [28]. While it has been shown that parents of children from Middle Eastern cultural backgrounds generally encouraged healthy behaviours, they also reported making regular exemptions [29].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous findings among Asian CALD youth in Australia and internationally, the present study found lower levels of PA 5,6,[16][17][18][19][20][21][22]38 and greater levels of SB 5,17,18,21 among Chinese Australian and South-east Asian adolescents compared with their non-CALD Anglo-Australian counterparts. To the best of our knowledge, this is the first study to objectively investigate differences in PA and SB participation among specific Asian Australian populations and highlights several concerns that warrant attention.…”
Section: Discussionsupporting
confidence: 91%
“…, O'Dea & Dibley , Achat & Stubbs , Hardy et al . ). The prevalence of overweight/obesity has been found to be higher among Australian children from Pacific Island, European, North African and Middle Eastern cultural backgrounds compared with their English‐speaking background peers.…”
Section: Introductionmentioning
confidence: 97%
“…, O'Dea & Dibley , Achat & Stubbs ), a NSW study showed that, among low SES children, there were clear differences in weight and weight‐related behaviours according to cultural background (Hardy et al . ). In particular, boys from Asian or Middle Eastern and a low SES background were significantly more likely to be obese compared with their peers from an English‐speaking background.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation